A review of different types of volunteer programs for older adults with and without cognitive impairment - Xianghe Zhu; Xianghe Zhu; Xianghe Zhu; Xianghe Zhu; Zhiwei Dong; Yili Wu; Yili Wu; Yili Wu; Yili Wu; Dong-Wu Xu; Dong-Wu Xu; Dong-Wu Xu (Frontiers Media S.A., 2023)
Theoretical models and empirical evidence suggest an association between volunteering and health outcomes in older adults. However, less is known about existing programs that involve older adults engaging in formal volunteering, especially programs for older volunteers with cognitive impairment. In this review, we summarized and evaluated different types of volunteering-based programs involving older volunteers with and without cognitive impairment. After a non-systematic literature search, we presented eight example volunteer programs. Older volunteers participate in the programs in person or remotely. In five of the programs, older volunteers without cognitive impairment participate in intergenerational engagement, support and referral, home visiting, and dementia care services. The other three programs specifically recruit older volunteers with cognitive impairment and provide intergenerational engagement and individualized volunteer activities. Both strengths and challenges identified in the programs were discussed. Different types of volunteering-based programs are available for engaging older volunteers. For volunteers to remain active during the pandemic or for volunteers who live with cognitive impairment, remote programs can be a valuable alternative. Program effects on older volunteers need to be tested in more rigorously designed studies.